2015
DOI: 10.5152/dir.2014.14217
|View full text |Cite
|
Sign up to set email alerts
|

Region of interest demarcation for quantification of the apparent diffusion coefficient in breast lesions and its interobserver variability

Abstract: ORIGINAL ARTICLEPURPOSE We aimed to compare two different methods of region of interest (ROI) demarcation and determine interobserver variability on apparent diffusion coefficient (ADC) in breast lesions. METHODSThirty-two patients with 39 lesions were evaluated with a 3.0 Tesla scanner using a diffusion-weighted sequence with several b-values. Two observers independently performed the ADC measurements using: 1) a small fixed area of 10 mm 2 ROI within the area with highest restriction; 2) a large ROI so as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 8 publications
1
37
0
Order By: Relevance
“…In a study of 81 patients with benign and malignant conditions of the anterior mediastinum, Priola et al found that ADC values of the OSR and MSR methods were significantly lower compared to all other methods that sampled the whole tissue on one or more transverse slices . However, both studies found excellent interobserver agreement in all methods . Notably, we obtained the highest repeatability in ADC measurements by using the WTV method.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…In a study of 81 patients with benign and malignant conditions of the anterior mediastinum, Priola et al found that ADC values of the OSR and MSR methods were significantly lower compared to all other methods that sampled the whole tissue on one or more transverse slices . However, both studies found excellent interobserver agreement in all methods . Notably, we obtained the highest repeatability in ADC measurements by using the WTV method.…”
Section: Discussionmentioning
confidence: 51%
“…Prior studies assessed the interobserver agreement of ADC quantification by using different methods in various tumors . However, none of the studies on DW‐MRI of pleural disease evaluated the measurement variability of the ADC between different readings or readers .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An ROI that covers all tumour volume minimizes the interobserver variability and differences between ADC calculations and ensures that the measurements are repeatable. 27,28 Therefore, we used the largest ROI which was not affected by artefacts.…”
Section: Discussionmentioning
confidence: 99%